2001
DOI: 10.1021/jo000560g
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Delocalization Contribution to the Anomeric Effect Evaluated by Computational Methods

Abstract: This study proposes the determination of the electronic delocalization contribution to the Anomeric Effect (EDCAE, Delta Delta E(deloc), eq 3) as a computational alternative in the evaluation of the excess of the axial preference shown by an electronegative substituent located at alpha position to the annular heteroatom of a heterocyclic compound (anomeric position) in both the presence and the absence of electronic delocalization retaining the same molecular geometry. The determination of the EDCAE is computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 55 publications
1
31
0
1
Order By: Relevance
“…Later, the enthalpic nature of this type of effect was established [42][43][44]. This phenomenon baffled the scientific community -weak anomeric effects were expected because of the low electron-donating nature of the atoms involved (from the second row of the periodic table) [45,46].…”
Section: Anomeric Effect On Heterocyclohexanesmentioning
confidence: 99%
“…Later, the enthalpic nature of this type of effect was established [42][43][44]. This phenomenon baffled the scientific community -weak anomeric effects were expected because of the low electron-donating nature of the atoms involved (from the second row of the periodic table) [45,46].…”
Section: Anomeric Effect On Heterocyclohexanesmentioning
confidence: 99%
“…If only steric effects are taken into account, the equatorial conformer should predominate, as has been shown by way of the delocalization energy contribution to the anomeric effect in similar segments. 11 Although the absolute energy values are different from the ones obtained including electronic delocalization, the tendencies remain the same, with ax-3 still being the highest rotamer in energy, due, of course to the high steric repulsions found between the OMe and the ring. This might be just another case showing the weakness in this analysis of population, due to its high sensibility as a calculation tool.…”
mentioning
confidence: 83%
“…The term anomeric effect was introduced in 1958 by Lemieux 5 and refers to the tendency of an electronegative substituent at C 2 of a pyranoid ring (see Scheme 1) to adopt the axial rather than the equatorial orientation, in contrast with expectations based exclusively on steric [8][9][10] Recently, the study of the contributions of the electronic delocalization to the anomeric effect showed that the observed axial/equatorial conformational preference is not solely of stereoelectronic origin 11 since the stereoelectronic interactions present in the axial conformer are as important as the ones in the equatorial arrangement. The anomeric effect in 2-MeO-oxane was found to be 1.7 kcal/mol, from the difference of ∆G o for the axial/equatorial equilibrium of 1, 0.9 kcal/mol, and the A Value for the methoxy group, -0.8 kcal/mol (2, Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…These values show the importance of these interactions. 16,17 On the other hand, according to Bader, 18 the existence of a bond critical point and the bond trajectory that connects this critical point with two nuclear attractors are a necessary and sufficient conditions for a bond to exist. From the point of view of molecular structure, only demonstrating its existence, it is possible to satisfactorily prove the presence of a hydrogen bond.…”
mentioning
confidence: 99%
“…The interactions between filled and vacant orbitals represent the deviation of the molecule from the Lewis structure and can be used as a measure of delocalization. 16,17 Wave functions were used to compute AIM atomic energies using the AIMPAC set of programs. …”
mentioning
confidence: 99%